ZnS THIN FILMS – AN OVERVIEW - Nadeem, M. Y.; Ahmed, Waqas; Wasiq, M. F. (Journal of Research (Science), 2005)
ZnS thin film properties are overviewed in this research paper. These include absorbance, transmittance, optical band gap, refractive index and structure (on the basis of X-ray diffraction and scanning electron microscopy). It has been observed that these film properties are dependent on various parameters e.g. thickness of the film, deposition method, deposition rate, substrate material, substrate temperature, source temperature etc. In most of the studies ZnS thin films showed the best preferential orientation of crystallinity to (111) plane of cubic structure, however, hexagonal structure is also observed. ZnS thin films are found useful in various device applications.